(untitled) (Research, Society and Development, 2025)
Objective: To identify the profile of the risk classification in the 24-hour Emergency Care Unit in the southern region of Brazil, correlating the sociodemographic characteristics of the population with data from the 3rd-quarter Management Report of the Municipal Health Department for 2023. Methodology: A documentary, descriptive, retrospective, and quantitative study, based on electronic medical records of patients treated between September 2023 and February 2024. Data collection was conducted in September and October 2024 through the TOTVS system, with descriptive percentage analysis. The study was approved by the ethics committee through Plataforma Brasil under opinion nº 7.083.286. Results: The data show that most of the patients are female (56.9%), with complaints related to the “Adult Malaise” flowchart (24%). The majority of cases were classified as "Low urgency" (green code), representing 74.8% of the visits. Conclusion: The results support the initial hypothesis that a significant portion of the demands for this Emergency Care Unit consists of low-complexity cases, which are sensitive to Primary Health Care. This highlights the need to strengthen Primary Health Care to reduce the burden on emergency and urgent services.